The X-ray crystallographic structure of the angiogenesis inhibitor angiostatin - Abad, M. C.; Arni, R. K.; Grella, D. K.; Castellino, F. J.; Tulinsky, A.; Geiger, J. H. (Elsevier B.V., 2002)
Angiogenesis inhibitors have gained much public attention recently as anti-cancer agents and several are currently in clinical trials, including angiostatin (Phase I, Thomas Jefferson University Hospital, Philadelphia, PA). We report here the bowl-shaped structure of angiostatin kringles 1-3, the first multi-kringle structure to be determined. All three kringle lysine-binding sites contain a bound bicine molecule of crystallization while the former of kringle 2 and kringle 3 are cofacial. Moreover, the separation of the kringle 2 and kringle 3 lysiner binding sites is sufficient to accommodate the a-helix of the 30 residue pepticle VEK-30 found in the kringle 2/VEK-30 complex. Together the three kringles produce a central cavity suggestive of a unique domain where they may function in concert. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: angiogenesis; plasminogen; coagulation; Crystal structure; kringle domains